Benzoyl transfer reactivities of racemic 2,4-Di-O-acyl-myo-inosityl 1,3,5-orthoesters in the solid state: molecular packing and intermolecular interactions correlate with the ease of the reaction - Sarmah, M. P.; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Chemistry-A European Journal, 2005)
Racemic 2,4-di-O-acyl-myoinosityl 1,3,5-orthoesters undergo transesterification catalyzed by sodium carbonate with varying ease of reaction in the solid state; reactions in solution and melt do not show such varied differences. An interesting crystal of a 1:1 molecular complex of highly reactive racemic 2,4-di-O-benzoyl-myo-inosityl 1,3,5-orthoformate and its orthoacetate analogue exhibited better reactivity than the latter component alone. Single-crystal X-ray structures of the reactants have been correlated with the observed differences in the acyl-transfer efficiencies in the solid state. Although each of the derivatives helically self-assembles around the crystallographic 2(1) axis linked through O-(HO)-O-... hydrogen bonding, the pre-organization of the reactive groups (C=O [El] and OH [Nu]), C-(HO)-O-... and the C=H(...)pi interactions are significantly more favourable for the reactive derivatives than the less reactive ones. Bond-length distributions also showed differences; the O-C bond of the axial benzoyl group, which gets cleaved during the reaction, is longer (1.345-1.361 angstrom) relative to the chemically equivalent O-C bond of the equatorial benzoyl group (1.316-1.344 angstrom) in the reactive derivatives. These bond-length differences are not significant in the less reactive derivatives. The overall molecular organization is different too; the strikingly discrete helices, which may be viewed as ``reaction tunnels'' and are held by interhelical interactions, are clearly evident in the reactive derivatives in comparison with the less reactive ones.
Keywords: hydrogen bonds; Inositol; solid-state reactions; structure elucidation; transesterification

Sulfonate protecting groups. synthesis of O- and C-methylated inositols: D- and L-ononitol, D- and L-laminitol, mytilitol and scyllo-inositol methyl ether - Sarmah, M. P.; Shashidhar, M. S.; Sureshan, K. M.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron, 2005)
Syntheses of D- and L-ononitol, D- and L-laminitol, mytilitol and scyllo-inositol methyl ether starting from myo-imositol are described. One or two of the inyo-inositol 1,3,5-orthoformate hydroxyl groups were protected as tosylates. These mono or ditosylates served as key intermediates for the preparation of O- and C-methyl inositols. Racemic 2,4-di-O-tosyl-myo-inositol 1,3,5-orthoformate was resolved as its diastereomeric camphanates. Use of sulfonate groups for the protection of inositol hydroxyl groups resulted in substantial improvement in the overall yield of O- and C-methyl inositols. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Cyclitol; Inositol; Orthoester; Protecting group; sulfonate